Recombinant Proteins Combining the Inter-domain Region of Pneumococcal Surface Antigen "A" and Adaptive W-type Polypeptide of Thermotoga Bacteria as a Potential Component Base for the Development of New Diagnostics and Genetically Engineered Subunit Vaccines against Pneumococcal Infection - Parfenova, O.K.; Sidorov, N.G.; Kasap, E.Y.; Kurkin, R.V.; Grishin, D.V. (Biomedical Chemistry: Research and Methods, 2024)
The problems related to the development of pneumococcal vaccines require combination of traditional solutions and alternative systems optimizing this procedure. Recombinant subunit vaccines have undeniable advantages over inactivated and live-attenuated vaccines: they induce cell-mediated and humoral immunologic responses effectively and with high specificity, but without the risks associated with authentic pathogen processing. However, subunit vaccines require specific adjuvants to enhance the immune response or special fusion partners to improve solubility, expression and optimize subsequent fine purification of the protein of interest. In the framework of this work, a structurally conserved region of the most immunogenic region of the vaccine-valuable surface antigen PspA of Streptococcus pneumoniae was chosen as a model protein, and the adaptive polypeptide CheW from the hyperthermophilic microorganism Thermotoga petrophila was used as a promising fusion protein. Appropriate expression plasmid vectors were designed in silico and constructed in vitro. Efficient E. coli producer strains were obtained and appropriate conditions for heterologous production of chimeric proteins were selected. The fusion partner from T. petrophila positively influenced the properties of the resulting constructs such as thermostability, solubility, and homogeneity. During this work, the optimal pH and temperature ranges of the created proteins were determined, and the principles of low-stage purification were elaborated. We obtained and characterized new proteins, which were not previously found in nature in a similar bioconfiguration. The results indicate that the biotechnologically valuable characteristics of the fusion protein were more expressed when the adaptive CheW protein was combined with the N-terminus of the PspA antigen.